Strategi Pengembangan Wisata Kramat Beach di Kabupaten Pulau Talibu, Maluku Utara - Mulae, Sunaidin Ode; Mansur, Mustafa (Pusat Studi Pariwisata Universitas Gadjah Mada, 2026)
This study aims to formulate development strategies for the Kramat Beach tourism destination in Kramat Village, Taliabu Island. The main issue examined is the low number of tourist visits, which necessitates strategies to enhance the destination’s attractiveness for both local and out-of-region tourists. The research employs a qualitative approach using Community-Based Tourism (CBT) and SWOT analysis. The results indicate that Kramat Beach possesses significant natural tourism potential, including white sandy Beaches, panoramic views of the two Kramat Islands, coral reefs, and clear seawater, as well as local vegetation such as coconut and Ketapang trees that enhance visitor comfort. Development strategies are implemented through digital promotion (YouTube, Instagram, and Facebook) and the provision of supporting amenities such as gazebos, nighttime lighting, and aesthetic photo spots. The SWOT analysis places the destination in Quadrant I (Aggressive Strategy) with an IFAS score of 2.70 and an EFAS score of 2.85, indicating strong internal strengths and high external opportunities. The SO strategy becomes the main focus, supported by WO, ST, and WT strategies, to enhance competitiveness, extend tourists’ length of stay, and encourage sustainable, community-based tourism development. The study concludes that the Kramat Beach tourism destination in Kramat Village, Taliabu Island Regency, has considerable tourism potential for further development. This potential includes the natural beauty of white sandy Beaches, clear seawater, marine biodiversity, and panoramic views of surrounding small islands that support the development of nature and marine tourism. In addition, the destination’s location, which is relatively close to the regency capital, provides ease of access for tourists and serves as a strategic advantage in regional tourism development.